Older age and depressive state are risk factors for re-positivity with SARS-CoV-2 Omicron variant - Li, Maojun; Peng, Huawen; Duan, Guangyou; Wang, Jian; Yu, Zhiqing; Zhang, Zhongrong; Wu, Liping; Du, Ming; Zhou, Shiji (Frontiers in Public Health, 2022)
Background: The reinfection rate of SARS-CoV-2 Omicron variant is high; thus, exploring the risk factors for reinfection is important for the effective control of the epidemic. This study aimed to explore the effects of psychological and sleep factors on reinfection with Omicron. Methods: Through a prospective cohort study, 933 adult patients diagnosed with Omicron BA.2.2 infection and testing negative after treatment were included for screening and follow-up. We collected data on patients’ demographic characteristics, SARS-CoV-2 Omicron vaccination status, anxiety, depression, and sleep status. Patients underwent nucleic acid testing for SARS-CoV-2 Omicron for 30 days. Regression and Kaplan-Meier analyses were used to determine the risk factors for micron reinfection of Omicron. Results: Ultimately, 683 patients were included in the analysis. Logistic regression analysis showed that age (P=0.006) and depressive status (P=0.006) were two independent risk factors for Omicron reinfection. The odds ratios of reinfection in patients aged≥60 years and with a Patient Health Questionnaire-9 (PHQ-9) score≥5 was 0.55 (95% confidence interval:0.36-0.85) and 0.45 (0.26-0.79), respectively. In addition, the time from infection to recovery was significantly longer in patients aged ≥60 years (17.2±4.5 vs.16.0±4.4, P=0.003) and in patients with PHQ-9≥5 (17.5±4.2vs.16.2±4.5, P=0.026). Kaplan–Meier analysis showed that there was a significantly higher primary reinfection rate in patients aged ≥60 years (P=0.004) and PHQ-9≥5 (P=0.007). Conclusion: This study demonstrated that age of ≥60 years and depressive status were two independent risk factors for reinfection with Omicron and that these factors could prolong the time from infection to recovery. Thus, it is necessary to pay particular attention to older adults and patients in a depressive state.